International organizations, advocacy coalitions, and domestication of global norms: Debates on climate change in Canada, the US, Brazil, and India. Issue 81 (March 2018) - Kukkonen, Anna; Ylä-Anttila, Tuomas; Swarnakar, Pradip; Broadbent, Jeffrey; Lahsen, Myanna; Stoddart, Mark C.J.
Highlights: The paper analyzes the centrality of international organizations and the opposition or support that they face from coalitions of national organizations in mass-mediated climate policy debates in four countries. International organizations are less central in the high-income countries that are high per capita emitters (Canada and the US) where there is more opposition to global norms from coalitions of national organizations. International organizations are more central in the middle-income countries that are low per capita emitters where there is less opposition to global norms. Position in the world society and the different commitments between Annex I and non-Annex I countries are likely to have shaped national debates on climate change. Abstract: National climate policies are shaped by international organizations (IOs) and global norms. Drawing from World Society Theory and the Advocacy Coalition Framework (ACF), we develop two related arguments: (1) one way in which IOs can influence national climate policy is through their engagement in mass-mediated national policy debates and (2) national organizations involved in the policy process may form advocacy coalitions to support or oppose the norms promoted by IOs. To examine the role of IOs in national policy debates and the coalitions that support and oppose them, we use discourse network analysis (DNA) on over 3500 statements in 11 newspapers in Canada, the United States (US), Brazil, and India. We find that in the high-income countries that are high per capita emitters (Canada and the US), IOs are less central in the policy debates and the discourse network is strongly clustered into competing advocacy coalitions. In the lower-income countries that are low per capita emitters (Brazil and India), IOs are more central and the discourse network is less clustered. Relating these findings to earlier research, we suggest that the differences we find between high and low per capita emitters may be to some extent generalizable to the relevant country groups beyond our four cases.